Anti-amoebic properties of carbonyl thiourea derivatives - Ibrahim, Maizatul Akma; Mohd Yusof , Mohd Sukeri; Mat Amin, Nakisah (MDPI, 2014)
Thiourea derivatives display a broad spectrum of applications in chemistry, various industries, medicines and various other fields. Recently, different thiourea derivatives have been synthesized and explored for their anti-microbial properties. In this study, four carbonyl thiourea derivatives were synthesized and characterized, and then further tested for their anti-amoebic properties on two potential pathogenic species of Acanthamoeba, namely A. castellanii (CCAP 1501/2A) and A. polyphaga (CCAP 1501/3A). The results indicate that these newly-synthesized thiourea derivatives are active against both Acanthamoeba species. The IC50 values obtained were in the range of 2.39–8.77 μg·mL-1 (9.47–30.46 μM) for A. castellanii and 3.74–9.30 μg·mL-1 (14.84–31.91 μM) for A. polyphaga. Observations on the amoeba morphology indicated that the compounds caused the reduction of the amoeba size, shortening of their acanthopodia structures, and gave no distinct vacuolar and nuclear structures in the amoeba cells. Meanwhile, fluorescence microscopic observation using acridine orange and propidium iodide (AOPI) staining revealed that the synthesized compounds induced compromised-membrane in the amoeba cells. The results of this study proved that these new carbonyl thiourea derivatives, especially compounds M1 and M2 provide potent cytotoxic properties toward pathogenic Acanthamoeba to suggest that they can be developed as new anti-amoebic agents for the treatment of Acanthamoeba keratitis.